Transition piece design for an onshore hybrid wind turbine with multiaxial fatigue life estimation. Issue 4 (August 2018) - Farhan, Muhammad; Mohammadi, Mohammad Reza Shah; Correia, José António; Rebelo, Carlos
Steel tubular structures are somewhat entrenched for the wind turbine towers. Recently, steel hybrid lattice/tubular towers are being investigated as a conceivable answer for taller onshore wind turbines for which convectional steel tubular towers are less competitive. Hybrid lattice/tubular towers require a transition piece which serves as a connection between lattice and tubular part. As the transition piece is supposed to transfer all the dynamic and self-weight loads to the lattice and foundation, these structural elements present unique features and are critical components to design and ought to resist strong cyclic bending moments, shear forces, and axial loads. Well-designed transition pieces with optimized ultimate state and fatigue capacities for manufacturing contribute to the structural soundness, reliability, and practicability of new onshore wind turbines hybrid towers. This research focuses on the investigation of the transition piece for an onshore wind turbine hybrid tower. The 5-MW reference wind turbine and a hybrid lattice/tubular tower were simulated in the servo-hydro aero-elastic analysis tool (by ASHES software) from which the loads and dynamic response of the supporting structure were obtained. Cross-sectional forces at the transition piece elevation were calculated and the connection with the lattice structure is designed. The transition piece was designed by finite element model considering ultimate limit load and fatigue load, using nonlinear analysis and multiaxial fatigue for life-time prediction, respectively. Multiaxial fatigue life was calculated based on Brown–Miller and Smith–Watson–Topper methods. In comparison, Smith–Watson–Topper method comes out to be more conservative. Potential of using high-strength steel S690 was investigated.